LANGUAGE SKILLS, LEARNING DIFFICULTIES, AND IDENTIFICATION ERRORS - Kayumova Shakhnoza Kabiljonovna; Alikulova Yulduz Shukhrat qizi ("Conference on Universal Science Research 2023", 2024)
Cases of instantial use may often seem to be vague, contradictory, and hard to grasp or analyse. Many types of instantial use may exert an inhibitory effect on the learner. L2 learners in particular may find it frustrating to deal with passages based on complicated patterns such as allusion or concurrent use, or working with more difficult newspaper texts, let alone sophisticated discourses such as Shakespeare’s plays, or doing diachronic studies.